2011
DOI: 10.1136/jech.2010.128116
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in the community setting: the neighbourhood as a source of ‘cognitive reserve’?

Abstract: Background Existing research has found a positive association between cognitive function and residence in a socioeconomically advantaged neighborhood. Yet, the mechanisms underlying this relationship have not been empirically investigated. This study tests the hypothesis that neighborhood socioeconomic structure is related to cognitive function partly through the availability of neighborhood physical and social resources (e.g. recreational facilities, community centers and libraries), which promote cognitively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
168
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 38 publications
10
168
2
Order By: Relevance
“…It is believed that elderly people who live in places with better socioeconomic conditions are likely to benefit more from physical, social and leisure activities available in these environments, which contributes to better cognitive function 14 . In addition, poorer neighborhoods may suffer more from the effects of crime, causing the elderly population to be socially and psychologically isolated within their community 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that elderly people who live in places with better socioeconomic conditions are likely to benefit more from physical, social and leisure activities available in these environments, which contributes to better cognitive function 14 . In addition, poorer neighborhoods may suffer more from the effects of crime, causing the elderly population to be socially and psychologically isolated within their community 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Perceptional overload, long term exposure to an environment, which is busy and interpreted as stressful and dangerous, may result in poorer cognitive outcomes or even social isolation (Cacioppo & Hawkley, 2009;Caparos et al, 2012;Clarke et al, 2012;Linnell, Caparos, de Fockert, & Davidoff, 2013). Not only overload but also lack of environmental stimulation could be detrimental for cognitive functions in older adults (Schooler, 1984;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…That offers a higher diversity of stimuli, therefore, requirements to make more decisions and bigger amount of information needs to be taken into account and processed (Schooler, 1984;Wörn et al, 2017). It is possible then to view this type of environment as a source of cognitive stimulation or even a brain training (Cassarino & Setti, 2015) and may potentially promote cognitive reserve (Clarke et al, 2012). Urban areas usually offer a living environment with a greater density of physical, social and institutional resources which may promote protective health behaviors and facilitate mental stimulation (Clarke et al, 2012(Clarke et al, , 2015Lee & Waite, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying environmental features related to cognition in later life may therefore reduce dementia occurrence by moderating individual risk factors. A small number of studies have reported that older people living in more deprived areas have a higher risk of cognitive impairment or decline that persists after adjusting for individual demographic factors [7][8][9]. Since area deprivation is a proxy for built and social environmental features in communities, this highlights the potential influence of the community environment on cognitive function in later life, as described by the theoretical framework in Figure 1.…”
Section: Introductionmentioning
confidence: 99%